Efeito do estresse hídrico e da época de plantio na produtividade de três cultivares de algodão herbáceo (Gossypium hirsutum L.) sob o regime de irrigação no vale do Curu - Souza, Francisco Alves de (1986)
This experiment was conducted in 1985, at Pentecoste-Ceará (Brasil), to study the response of three upland cotton cultivar (Gossypium hirsutum L.).-BR1-C2, CNPA 76-6873 and CNPA 78-SME4, sown at five different times of planting (july/09 E1) and 24 (E2); august/08 (E3) and 23 (E4) and september/07 (E5), and four levels of water stress: 1) irrigated each 20 days, the first 2 at the vegetative phase, two during flowering/fruting and the last one during maturation; 2) irrigated at 20, 40, 60 and 80 days after planting (dap) two irrigations in the vegetative phase and two during flowering/fruting phases; 3) irrigated at 60 and 80 days heing both irrigations in the flowering/fruting phases; and 4) irrigated once at 120 dap, during maturation. The experimental design was a split-split-plot one with 60 treatments with two replications each in factorial scheme 5 x 4 x 3, being 5 times of planting, 4 levels of water stress and 3 cultivars. Water was applied by blocked furrows and measured by hydrometer. The effect of time of planting on cotton production and fiber strength, was higher on the time, of planting E3 with 1,568.9 kg/ha, and difering statistically from the E1 and E5. There was influence of water stress and cultivar on yield, weight of 100 seeds, boll weight and technological fiber charater. The higher yield was obtained by the water stress (I2) (1535,9 kg/ha) although it did not differ from the (l1) (1480,4 kg/ha). The CNPA 76-6873 cultivar presented the higher yiel, 1500 kg/ha but it showed lower values of weight of 100 seeds, boll weight and fiber strength, and resistence.